2004
DOI: 10.1163/156854004774248681
|View full text |Cite
|
Sign up to set email alerts
|

Larval Stages of the Blue Swimmer Crab, Portunus Pelagicus (Linnaeus, 1758) (Decapoda, Brachyura)

Abstract: Larvae of Portunus pelagicus (Linnaeus, 1758) were reared in the laboratory on hatching from wild ovigerous females collected from Palk Bay, southeast India. The larval stages included four zoeal stages and one megalopa. The megalopa moulted to the first crab instar. The zoeae and megalopa were very similar to those of other portunids. The duration of each of the first two zoeal stages was 3-4 days, the following two stages 2-3 days, and the megalopa 3-5 days, reaching the first crab stage in 15-17 days. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…It has high potential for aquaculture because of its rapid growth rate (Josileen and Menon, 2004), ease of larviculture, high fecundity, and relatively high tolerance to nitrate and ammonia (Bryars and Havenhand, 2006;Zeng, 2007a,b,c, 2008). P. pelagicus is commercially cultivated in some areas, such as Thailand .…”
Section: Introductionmentioning
confidence: 99%
“…It has high potential for aquaculture because of its rapid growth rate (Josileen and Menon, 2004), ease of larviculture, high fecundity, and relatively high tolerance to nitrate and ammonia (Bryars and Havenhand, 2006;Zeng, 2007a,b,c, 2008). P. pelagicus is commercially cultivated in some areas, such as Thailand .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in recent years shrimp culture has encountered heavy losses due to disease outbreaks in Asia, which warrants the need to diversify culture operations in order to utilize the farm and to include other biologically suitable and economically viable crustaceans in the production process. The authors have studied the complete larval development of the species in an elaborative way (Josileen & Menon, 2004) and mass seed production technology has also been developed (Josileen, 2001). The present study provides information on the suitability of the blue swimmer crab for mariculture.…”
Section: Introductionmentioning
confidence: 99%
“…Other study of Ikhwanuddin et al, (2012 b ) in which larvae were reared at various density from 50-300 larvae per litre, they found the larvae reached megalopa phase on day-13. Josileen and Menon (2004) also reported that crab-1 stage of blue crab was attined on day-15-17. These all founding indicated that domesticated broodstock-raised larvae developed faster compared to the wild broodstock-raised larvae.…”
Section: Resultsmentioning
confidence: 89%